Evaluation of tubotympanic angle of Eustachian tube and its relationship with Eustachian tube function in patients with chronic middle ear infection - Davoodi, Farzin; Abbasi, Zahra; Khosravi Farsani, Pejman; Eftekharian, Ali; Bazgir, Narges (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: chronic otitis media is characterized by the accumulation of fluid in the middle ear and behind the tympanic membrane without signs of acute infection. The association between a middle ear infection and anatomical and physiological disorders of the Eustachian tube has been reported in several studies and its malfunction is one of the main causes of middle ear infection. Aim: We aim to find the relation of tubotympanic angle of Eustachian tube and chromic otitis media. Methods: In this study, 100 patients with chronic unilateral middle ear infections were included. To determine the tubotympanic angle of the Eustachian tube, a temporal bone CT scan was used in the radiology department of Loghman Hospital. Eustachian tube angle and ear function were recorded. Results: Among the 100 patients in the study, 42 were men and 58 were women. The mean age of patients in the study was 39.64±12.64 years. The angle was 3.79 ± 34.27 in the healthy ear and 2.43 ± 31.06 in the diseased ear, which showed a statistically significant difference between the two groups Conclusion: Eustachian tube angles in adults may play an important role in the cause of chronic otitis media. In this study, it was found that the horizontalization of the Eustachian tube is associated with chronic otitis media. Besides, determining the angle of the Eustachian tube can help determine the susceptibility to otitis media.